Ligneous cervico-vaginitis mimicking female genital tract malignancies - Mehmet Sait Bakır; Özer Birge; Ceyda Karadag; Can Dinc; Ahmet Boduroglu; Tayup Simsek (Clinical and Experimental Obstetrics & Gynecology)
Background: Ligneous cervicitis is a rarely reported disease in the literature, and it is commonly misdiagnosed as genital cancer. Patients with ligneous cervicitis can have multiple systemic problems. The lesions resemble malignancies. Multiple biopsies are essential for the diagnosis. Herein, we present 2 cases of ligneous cervicitis, both of which had plasminogen deficiency. Our aim in this report was to discuss these cases with guidance of the literature. Conclusion: Ligneous cervicitis commonly mimics female genital cancers. Hence, it is very important to utilize a multidisciplinary approach in making a differential diagnosis.